Emergence of optrA-mediated linezolid resistance in clinical isolates of Enterococcus faecalis from Argentina - Gagetti, Paula Silvana (2023)
Objectives: The aim of this study was to characterize the first 14 optrA-carrying linezolid resistant E. faecalis clinical isolates recovered in seven Argentinian hospitals between 2016 and 2021. The epidemiology of optrA-carrying isolates and the optrA genetic context were determined. Methods: The isolates were phenotypically and genotypically characterized. Susceptibility to 13 antimicrobial agents was performed; clonal relationship was assessed by pulsed field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Data provided by the whole-genome sequencing were used for identification of sequence types, antimicrobial resistance genes, optrA variants, phylogenetic tree, and mobile genetic elements responsible to the dissemination of these strains. Results: All the optrA-carrying E. faecalis isolates were multidrug-resistant and harboured several antimicrobial resistance genes. They carried three optrA variants and belonged to different lineages; however, three of them belonged to the hyperepidemic CC16. Mobile genetic elements were detected in all the isolates. The analysis of the optrA flanking region suggests the plasmidic localization in most of the isolates. Conclusions: To the best of our knowledge, this is the first report of optrA-mediated linezolid resistance in Argentina. The emergence and dissemination of the optrA genes in clinical E. faecalis isolates are of concern and highlights the importance of initiating the antimicrobial surveillance of Enterococcus spp. under a One Health strategy.